Effects of Tax Depreciation Rules on Firms' Investment Decisions in an Inflationary Phase: Comparison of Net Present Values in Selected OECD Countries - Chang Woon Nam (Center for Economic Studies and ifo Institute (CESifo), 2001)
This study compares incentive effects of various tax depreciation methods which are currently employed in selected OECD countries. Their generosity is determined on the basis of Samuelson's true economic depreciation. For this purpose, the present value model is applied. The central issue is that the so-called historical cost accounting method, which is adopted in practice when calculating the corporate tax base, causes fictitious profits in inflationary phases that should also be taxed. Therefore, in periods with inflation generous tax depreciation provisions do not adequately promote private investment as designed, but partly compensate such losses caused by inflation.
Keywords: 330; true economic depreciation; tax depreciation rules; corporate tax; investment decision; net present value model; inflation; OECD